2014
DOI: 10.1007/s00167-014-2891-y
|View full text |Cite
|
Sign up to set email alerts
|

Intercondylar notch size influences cyclops formation after anterior cruciate ligament reconstruction

Abstract: Case-control study, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 42 publications
3
57
0
3
Order By: Relevance
“…The MRI is of low to isointense signal intensity in relation to skeletal muscle on both T1-and T2-weighted pulse sequences. [8][9][10][11][12] These MRI findings were consistent with those identified in our patient. The ACL graft fibers are typically seen as a low signal intensity except 4-8 months postoperatively, when the graft may appear iso-to hyperintense on fluid-sensitive imaging (T2, fat suppression) because of revascularization and synovialization.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The MRI is of low to isointense signal intensity in relation to skeletal muscle on both T1-and T2-weighted pulse sequences. [8][9][10][11][12] These MRI findings were consistent with those identified in our patient. The ACL graft fibers are typically seen as a low signal intensity except 4-8 months postoperatively, when the graft may appear iso-to hyperintense on fluid-sensitive imaging (T2, fat suppression) because of revascularization and synovialization.…”
Section: Discussionsupporting
confidence: 91%
“…1 However, 1 study found that physical therapy and graft placement were not related to the degree of severity of cyclops formation. 3 Fujii et al 9 found that a smaller cross-sectional area of the femoral intercondylar notch post-ACL reconstruction, as measured on MRI, was significant in the formation of cyclops lesions, confirming the importance of adequate notchplasty (surgical enlargement of the intercondylar notch) during ACL reconstruction.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Many methods of notch size measurements on imaging have been described. 2,[8][9][10] However, most methods have been used to study the relationship of notch size to ACL injury, and few have tried to reproduce arthroscopic measurements. Zeng et al 11 performed a meta-analysis of 16 studies assessing the correlation between intercondylar notch size and the risk of ACL injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, the methodology in the included studies varied greatly. Some studies measure absolute notch width, 2,9,12,13 whereas others measure notch width relative to the size of the femoral condyles. [14][15][16] Furthermore, different studies have measured these parameters on radiography, MRI, and CT scanning with little standardization.…”
Section: Discussionmentioning
confidence: 99%